Comparative Test of Ret-He Examination in Diagnosis of Iron Deficiency in Pregnant Women - Gilang Nugraha; Nur Masruroh; Diyan Wahyu Kurniasari (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2020)
The most common cause of anemia is iron deficiency, which found in 50% of anemia cases. There are 66.7% of pregnant women in Indonesia that still lack iron intake. Reticulocyte hemoglobin equivalent (Ret-He) examination as a single parameter is the initial indicator of iron deficiency, considered more sensitive in detecting iron reserves in the body. This study aims to determine the effectivity of the Ret-He examination as a single parameter in establishing the diagnosis of iron deficiency in pregnant women. This research was conducted on 30 pregnant women. The sensitivity, specificity, and predictive value of Ret-He were determined by comparing the results of the biochemical examination of iron profiles. Iron deficiency defined as an abnormal examination result on two or more biochemical parameters, which were SI 425 µg/dL, serum ferritin